1983
DOI: 10.1111/j.1439-0434.1983.tb00576.x
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Changes in the Chloroplast Ultrastructure in Abutilon Mosaic Virus (AbMV) infected Abutilon spec. (Malvaceae)

Abstract: Various kinds of pathological effects of the Abutilon Mosaic Virus (AbMV) in seasonal dependency have been observed on the macroscopic as well as on the microscopic level. The annual rhythmic fluctuation of light caused by the varying length and intensity of light incidence is directly correlated with the realization of symptoms, leading to an intensification of the leaf mosaic and to an increase in the light leaf areas during the summer. These macroscopic observations are correlated with an annual change in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

1987
1987
2019
2019

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 25 publications
2
14
0
Order By: Relevance
“…2) revealed that these fractions were free of mitochondria, and there were no virus-related structures that copurified with plastids. The ultrastructure of plastids from infected plants present in band C was similar to that of degenerated plastids, which are generally found in the yellow mosaic regions of the mesophyll (11,17) (Fig. 2B).…”
Section: Resultsmentioning
confidence: 72%
See 2 more Smart Citations
“…2) revealed that these fractions were free of mitochondria, and there were no virus-related structures that copurified with plastids. The ultrastructure of plastids from infected plants present in band C was similar to that of degenerated plastids, which are generally found in the yellow mosaic regions of the mesophyll (11,17) (Fig. 2B).…”
Section: Resultsmentioning
confidence: 72%
“…Ultrathin sections of leaf tissue had shown that plastids lose their lamellar structure and part of their stability (11,17). This could explain why DNA from other geminiviruses was not found in these organelles, unless the AbMV is an exception.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, with Abutilon mosaic virus (AbMV) and Sida micrantha mosaic viruses (SimMVs), light intensity as well as the daily amount of light influenced the macroscopic symptoms, as well as the ultra-structure of plastids (Jeske, 1986;Werz, 1978, 1980;Schuchalter-Eicke and Jeske, 1983). It was therefore of interest to investigate the light dependence for virus infection in A. gangetica plants.…”
Section: Symptoms and Virus Segregationmentioning
confidence: 98%
“…It is unclear whether they contain virus particle protein. By comparison with these effects on nuclei, few whitefly-transmitted geminiviruses are known to have large effects on cytoplasmic constituents other than chloroplasts, which, however, may be greatly affected (Jeske & Werz, 1978;Schuchalter-Eicke & Jeske, 1983).…”
Section: Introductionmentioning
confidence: 99%